An Entrepreneurial Lens on a Comparison of Indonesian Trendy Beverage Franchises - Respati Wulandari (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This paper compares local and foreign trendy beverage companies operating in Indonesia, examining their strategies and early-stage performance through an entrepreneurial orientation lens. Using secondary data from credible industry reports and publications, the study evaluates how each type of firm approaches market expansion, builds competitive advantage, and responds to industry challenges. Both local and foreign beverage companies have experienced rapid growth in recent years, yet many continue to report net losses during their initial operational periods. Local brands such as Fore Coffee and Kopi Kenangan benefit from strong cultural alignment and deep insight into Indonesian consumer preferences, enabling them to scale quickly in the domestic market. In contrast, foreign brands like Chagee and Chatime typically pursue international expansion only after achieving stability in their home countries, leveraging standardized global branding strategies to strengthen their overseas presence. By analyzing these strategic differences, the study highlights key entrepreneurial dimensions—innovation, proactiveness, and calculated risk-taking—that shape each company’s trajectory. The findings provide practical insights for emerging beverage enterprises seeking to design effective market-entry and growth strategies within a competitive and evolving industry.